PERTIMBANGAN HAKIM DALAM PENJATUHAN HUKUMAN TERHADAP TINDAK PIDANA PEMBUNUHAN BERENCANA (Studi Putusan Nomor 175/Pid.B/2020/PN Gst) - Artis Duha (Jurnal Panah Hukum, 2022)
Premeditated murder is a form of crime against life as regulated in Article 340 of the Criminal Code. Based on this, the formulation of the problem in this study is how the judge's consideration in the sentencing of the crime of premeditated murder in the decision number 175/Pid.B/2020/PN Gst. The type of research used in this research is normative legal research with a statutory approach method, case approach method and analytical approach method. Data collection techniques in this study using literature study, namely by collecting and analyzing secondary data. The secondary data consists of primary legal materials, secondary legal materials, and tertiary legal materials. The data analysis used in this research is qualitative data analysis with a descriptive approach. Based on the results of the research that the criminal conviction of the perpetrators of premeditated murder has been legally and convincingly proven to violate the provisions of Article 340 of the Criminal Code as stated in the indictment of the public prosecutor. The panel of judges sentenced the defendant to 10 (ten) years in prison as stipulated in Article 183 of the Criminal Procedure Code. The prison sentence that has been handed down by the judge cannot provide a sense of justice, especially for the victim, and the judge's decision cannot implement the purpose of giving the sentence. The author suggests that judges should be more thorough, careful and professional and should give maximum punishment to the defendant in accordance with the provisions of criminal law, in order to provide a deterrent effect to the perpetrators and other communities and the demands of the public prosecutor in prosecuting the accused must be maximally in accordance with the criminal provisions contained in Articles that ensnare the defendant or in accordance with the provisions of criminal law that are commensurate with the actions of the defendant